Long-term Feto-Maternal Microchimerism : Nature's Hidden Clue for Alternative Donor Hematopoietic Cell Transplantation? - Ichinohe, Tatsuo; Maruya, Etsuko; Saji, Hiroh (International journal of hematology, 2002)
During pregnancy, fetal hematopoietic cells carrying paternal human leukocyte antigens (HLA) migrate into maternal circulation, and, vice versa, maternal nucleated cells can be detected in fetal organs and umbilical cord blood, indicating the presence of bidirectional cell traffic between mother and fetus. By taking advantage of fluorescence in-situ hybridization or polymerase chain reaction-based techniques, researchers recently found that postpartum persistence of such reciprocal chimerism was common among healthy individuals and may sometimes cause tissue chimerism. Although the biological significance of long-lasting feto-maternal microchimerism is unknown, a number of investigations have suggested its association with the development of "autoimmune" diseases such as systemic sclerosis. However, the very common presence of feto-maternal microchimerism among subjects without any autoimmune attack may allow us the more appealing hypothesis that it is an indicator for the acquired immunological hyporesponsiveness to noninherited maternal or fetal HLA antigens. An offspring's tolerance to noninherited maternal antigens has been clinically suggested by the retrospective analysis of renal transplantations or haploidentical hematopoietic stem cell transplantations, and whether postpartum mothers can tolerate paternally derived fetal antigens is an intriguing question. Although an exact linkage between microchimerism and transplantation tolerance is yet to be elucidated, long-term acceptance of a recipient's cell in the donor may have a favorable effect on preventing the development of severe graft-versus-host disease, and the donor cell microchimerism in the recipient might facilitate the graft acceptance. If this concept holds true, HLA-mismatched hematopoietic stem cell transplantation would be more feasible among haploidentical family members mutually linked with feto-maternal microchimerism. Further studies are warranted to investigate the potential role of feto-maternal microchimerism in human transplantation medicine.